KREATIVITAS GURU MENGENALKAN HURUF HIJAIYAH PADA MATA PELAJARAN BACA TULIS ALQURAN KELAS I MADRASAH IBTIDAIYAH SWASTA TARBIYAH TEBAS TAHUN PELAJARAN 2024-2025 - Rati Rania; Dewi Ferawati; Muspian (TARBIYATUL ILMU: JURNAL KAJIAN PENDIDIKAN, 2026)
This study was initiated by the discovery of a unique phenomenon in Grade I at Tarbiyah Tebas Private Islamic Elementary School concerning teacher creativity in introducing Hijaiyah letters in the Qur'an Reading and Writing subject. The purpose of this study was to identify and analyze: (1) the forms of teacher creativity in introducing Hijaiyah letters in the Qur'an Reading and Writing subject for Grade I students at Tarbiyah Tebas Private Islamic Elementary School in the 2025–2026 academic year, and (2) the ability of Grade I students to recognize Hijaiyah letters at Tarbiyah Tebas Private Islamic Elementary School in the 2025–2026 academic year. This research employed a qualitative approach with a phenomenological research design. Data were collected through observation, interviews, and documentation. The data analysis techniques used were data condensation, data display, and conclusion drawing. The validity of the data was examined through source triangulation, technique triangulation, and member checking. The results of the study indicate that: (1) teacher creativity in introducing Hijaiyah letters in the Qur'an Reading and Writing subject for Grade I students was demonstrated through the use of various learning methods, such as the Iqra’ method, Hijaiyah letter card media, coloring activities, and singing Hijaiyah letters. (2) The ability of students to recognize Hijaiyah letters includes: (a) being able to mention Hijaiyah letters, (b) being able to distinguish Hijaiyah letters, and (c) being able to differentiate between Hijaiyah letters that are similar in form, although some students still experience difficulties.